2022
DOI: 10.1177/09612033221098533
|View full text |Cite
|
Sign up to set email alerts
|

The in vitro effects of vitamin 1, 25(OH) 2 D3 on expression of cytokines: In new-onset systemic lupus erythematosus patients

Abstract: Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease affecting a variety of factors in the immune system. Awareness of the role of cytokines in SLE has led to new clinical perspectives in its pathogenesis; therefore, the aim of this study was to investigate the effect of vitamin 1, 25(OH) 2 D3 (D3) on the expression of IL-2, IL-4, IL-5, IL-10, and IFN-γ cytokines in patients with lupus. Methods: A total of 65 new-onset SLE patients were enrolled in the study. After peripheral blood mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
(48 reference statements)
0
2
0
Order By: Relevance
“…Vitamin D exerts immunomodulatory properties that potentially influence its pathogenesis. Vitamin D also plays an important regulatory role in the innate and adaptive immune responses, while accumulating evidence suggests that vitamin D deficiency disrupts immune responses and contributes to the development of autoimmune conditions 39 . In the context of SLE, a study conducted in Indian patients with SLE reported a negative correlation between vitamin D levels and various disease‐related factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitamin D exerts immunomodulatory properties that potentially influence its pathogenesis. Vitamin D also plays an important regulatory role in the innate and adaptive immune responses, while accumulating evidence suggests that vitamin D deficiency disrupts immune responses and contributes to the development of autoimmune conditions 39 . In the context of SLE, a study conducted in Indian patients with SLE reported a negative correlation between vitamin D levels and various disease‐related factors.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D also plays an important regulatory role in the innate and adaptive immune responses, while accumulating evidence suggests that vitamin D deficiency disrupts immune responses and contributes to the development of autoimmune conditions. 39 In the context of SLE, a study conducted in Indian patients with SLE reported a negative correlation between vitamin D levels and various disease-related factors. These factors include activity, presence of anti-dsDNA antibodies, plasma (IFN)α levels IFN-gene expression.…”
Section: Discussionmentioning
confidence: 99%